Field notes contributed by Thomas H. Kent, spring 1980 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1980)
List of birds and locations contributed by Thomas H. Kent with observers Thomas K. Shires, Carl J. Bendorf, Thomas J. Staudt and W. Ross Silcock. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1980. Epson - sheet feed/flatbed